2021
DOI: 10.1101/2021.01.06.20249026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent dissemination of SARS-CoV-2 through the Uruguayan-Brazilian border

Abstract: SummaryBackgroundUruguay is one of the few countries in the Americas that successfully contained the COVID-19 epidemic during the first half of 2020. Nevertheless, the intensive human mobility across the dry border with Brazil is a major challenge for public health authorities. We aimed to investigate the origin of SARS-CoV-2 strains detected in Uruguayan localities bordering Brazil as well as to measure the viral flux across this ∼1,100 km uninterrupted dry frontier.MethodsUsing complete SARS-CoV-2 genomes fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…We speculate a trend towards the perpetuation and diversification of the lineages found in this study (B.1.1.248 and B.1.1.33) inside Brazil. The dissemination of these lineages were also reported in the Uruguayan-Brazilian border, driving viral introductions mainly from Southeast and Southern Brazil (especially RS state) to Uruguay [72]. In this study, we found consistent results, mainly regarding B.1.1.33 diffusion from Southern and Southeast to South-American countries (e. g. Argentina, Chile and Uruguay).…”
Section: Discussionsupporting
confidence: 84%
“…We speculate a trend towards the perpetuation and diversification of the lineages found in this study (B.1.1.248 and B.1.1.33) inside Brazil. The dissemination of these lineages were also reported in the Uruguayan-Brazilian border, driving viral introductions mainly from Southeast and Southern Brazil (especially RS state) to Uruguay [72]. In this study, we found consistent results, mainly regarding B.1.1.33 diffusion from Southern and Southeast to South-American countries (e. g. Argentina, Chile and Uruguay).…”
Section: Discussionsupporting
confidence: 84%
“…The B.1.1.33 lineage was studied in further details using 190 genomes from 13 Brazilian states, showing its variable abundance in different states (ranging from 2% in Pernambuco to 80% in Rio de Janeiro), and its moderate prevalence in South American countries (5-18%). Surprisingly, this lineage was firstly detected in early-March in other American countries ( e. g ., Argentina, Canada, and USA), and additional analysis suggest that an intermediate lineage (B.1.1.33-like) most probably arose in Europe and was later disseminated to Brazil, where its spread gave origin to lineage B.1.1.33 (Resende et al 2021) and possibly seeded secondary outbreaks in Argentina and Uruguay (Resende et al 2021; Mir et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…4 Southeast Brazil, on 9 March 2020 and then disseminated across the country 16,24,37,38 . This lineage was also associated with outbreaks in Argentina and Uruguay, countries bordering RS 38,39 .…”
Section: Temporal and Spatial Dynamics Of Sars-cov-2 Lineagesmentioning
confidence: 89%